2017
DOI: 10.4172/2332-2543.1000192
|View full text |Cite
|
Sign up to set email alerts
|

Fish Community Structure of Sandha River: A Link Analysis towards Fisheries Management and Conservation

Abstract: Sandha River water regime is used as a nursery, feeding and breeding places by commercially important fish species due to the presence of unique environment. Therefore, the present study has been conducted to assess water quality parameters, fish species abundance, fish diversity indices, conservation issues and management policy to guard the valuable aquatic resources of Sandha River from March 2015 to February 2016. Among the water quality parameters, temperature and pH were found at a slight rising level wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hanif et al [17] identified a total of 26 endangered species from the Sandha river. Ruma et al [11] performed a bimonthly 1 year research on the fishery resources of the Sandha river and reported 55 species of fish, these results indicating an increase in diversity in the coastal water over the past several years. Actually, as a result of certain recent incentive-based management approaches, the quantity of fish species has grown significantly, and fishermen are capturing many fish [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hanif et al [17] identified a total of 26 endangered species from the Sandha river. Ruma et al [11] performed a bimonthly 1 year research on the fishery resources of the Sandha river and reported 55 species of fish, these results indicating an increase in diversity in the coastal water over the past several years. Actually, as a result of certain recent incentive-based management approaches, the quantity of fish species has grown significantly, and fishermen are capturing many fish [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of just counting the number of species within a community, diversity indexes serve as a tool for more accurate information provision. As far as we can tell, only the studies of Hanif et al [17] and Ruma et al [11] have documented fish composition and biodiversity indices in the Sandha river in Bangladesh. However, they did not work on the correlation between fish and their environment.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Water turbidity and velocity can also impact fish community structure. Water transparency in flu-vial systems is affected by season, rainfall patterns, and water velocity [ 42 ], whereas current velocity is controlled by season, altitude, and morphological structure [ 42 ]. Meteorology and microclimatic drivers also influence hydrology of the study sites in the Karun with depth of water increasing from upstream to downstream sites.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides information about the community structure and spatial variation of the fish species in the Karun River basin. Fish species vary in their sensitivity to human intervention, natural calamities and environmental degradation in general [ 42 , 47 – 50 ]. The majority of fish species observed in our study belonged to the Cyprinidae and Leuciscidae families.…”
Section: Discussionmentioning
confidence: 99%